2013
DOI: 10.1002/chem.201204465
|View full text |Cite
|
Sign up to set email alerts
|

Unimolecular Reaction Mechanism of an Imidazolin‐2‐ylidene: An iPEPICO Study on the Complex Dissociation of an Arduengo‐Type Carbene

Abstract: The photoionization and dissociative photoionization of Im(iPr)2, 1,3-diisopropylimidazolin-2-ylidene, was investigated by imaging photoelectron photoion coincidence (iPEPICO) with vacuum ultraviolet (VUV) synchrotron radiation. A lone-pair electron of the carbene carbon atom is removed upon ionization and the molecular geometry changes significantly. Only 0.5 eV above the adiabatic ionization energy, IEad =7.52±0.1 eV, the carbene cation fragments, yielding propene or a methyl radical in parallel dissociation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 93 publications
0
47
0
Order By: Relevance
“…This hints to a common rate limiting transition state for at least some of the channels, as was observed in the past for other systems as well. 38,39 A summary of the parallel dissociation channels and the accompanying co-fragments is shown in Table 1.…”
Section: Breakdown Diagrammentioning
confidence: 99%
“…This hints to a common rate limiting transition state for at least some of the channels, as was observed in the past for other systems as well. 38,39 A summary of the parallel dissociation channels and the accompanying co-fragments is shown in Table 1.…”
Section: Breakdown Diagrammentioning
confidence: 99%
“…A mass spectrum of the isolated carbene ( m / z= 180) is depicted in Figure S1 (Supporting Information), showing some dissociative photoionization. Loss of isobutene (C 4 H 8 ) is the most important fragmentation pathway, indicating a behavior similar to i Pr 2 Im …”
Section: Resultsmentioning
confidence: 97%
“…examined in a synchrotron radiation (SR) study the dissociative photoionization of an iso ‐propyl substituted NHC and found two parallel dissociation pathways in the cation. Furthermore, they confirmed that ionization to the cationic ground state takes place from the in‐plane σ‐orbital at the carbene center . In addition, they investigated the ring‐expansion reaction of 1,3‐di‐methyl‐imidazoline‐2‐ylidene .…”
Section: Introductionmentioning
confidence: 84%
“…This excess energy and the original thermal energy of the sample was available for fragmentation. When studying dissociative photoionization processes, the threshold ionization fractional parent and daughter ion abundances were plotted in the breakdown diagram, which often contains clues as to the fragmentation mechanism, and can be modeled quantitatively using statistical thermodynamics approaches to determine accurate dissociative photoionization thresholds . Furthermore, owing to the long acceleration region and low extraction field, it took several microseconds for the photoions to reach their terminal velocity in the mass spectrometer.…”
Section: Methodsmentioning
confidence: 99%